2016
DOI: 10.1093/brain/aww243
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain analysis reveals increased neuroanatomical asymmetries in dementia for hippocampus and amygdala

Abstract: Structural magnetic resonance imaging data are frequently analysed to reveal morphological changes of the human brain in dementia. Most contemporary imaging biomarkers are scalar values, such as the volume of a structure, and may miss the localized morphological variation of early presymptomatic disease progression. Neuroanatomical shape descriptors, however, can represent complex geometric information of individual anatomical regions and may demonstrate increased sensitivity in association studies. Yet, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
126
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 61 publications
18
126
0
Order By: Relevance
“…Our findings were consistent with previous investigations [5,24,25] in that patients with AD did not differ from nondemented participants on global thalamic asymmetries. A breakdown by subnuclei, however, revealed lateralization of atrophy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with previous investigations [5,24,25] in that patients with AD did not differ from nondemented participants on global thalamic asymmetries. A breakdown by subnuclei, however, revealed lateralization of atrophy.…”
Section: Discussionsupporting
confidence: 93%
“…The cerebral atrophy characteristic of AD is bilateral but may not be symmetrical across hemispheres. With the advent of high‐resolution magnetic resonance imaging (MRI), detailed brain atlases, probabilistic models of neuroanatomy, and advanced neuroimaging segmentation tools, there is a growing body of evidence that AD is asymmetrical [2–5]. This has been supported by studies which have found that AD is associated with asymmetrical cortical thinning [2], cortical surface area [3], and global cerebral atrophy [4] across hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction effect is not significant for right CA2_3 and CA4_DG, although they also showed significant atrophy and correlation with MoCA. This result may suggest asymmetry of AD pathology, as previously reported [43, 44]. …”
Section: Discussionsupporting
confidence: 83%
“…White matter association tracts and frontopolar cortex are critically included in the network [123]. White matter integrity of the target regions is key for a correlation to performance on the Wechsler Intelligence Scales, both in young and adults [138,139]. The study in Mexico city, children exposed to pollution projects possibility of differential regional effects of inflammatory cytokines in brain.…”
Section: Neuropsychiatric Impact Of Pollutionmentioning
confidence: 99%